Optical diagnosis of diminutive polyps in the Dutch Bowel Cancer Screening Program: Are we ready to start? - van de Wetering, Alouisa J.P.; Meulen, Lonne W.T.; Bogie, Roel M.M.; van der Zander, Quirine E.W.; Reumkens, Ankie; Winkens, Bjorn; Cheng, Hao Ran; Straathof, Jan-Willem A.; Dekker, Evelien; Keulen, Eric; Bakker, C. M.; Hoge, Chantal; de Ridder, Rogier; Masclee, Ad A.M.; Sanduleanu-Dascalescu, Silvia (Endoscopy International Open, 2020)
Background and study aims Implementation of optical diagnosis of diminutive polyps may potentially increase the efficacy and cost-effectiveness of colonoscopies. To adopt such strategy in clinical practice, the Preservation and Incorporation of Valuable endoscopic Innovations (PIVI) thresholds provide the basis to be met: ≥ 90 % negative predictive value (NPV) for diagnosis of adenomatous histology and ≥ 90 % agreement on surveillance intervals. We evaluated this within the Dutch Bowel Cancer Screening Program (BCSP).Patients and methods Endoscopic and histological data were collected from participants of the national bowel cancer screening program with an unfavorable fecal immunochemical test referred for colonoscopy between February 2014 and August 2015 at four endoscopy centers. The “resect and discard” scenario was studied, resecting diminutive polyps without histological evaluation. Agreement between optical diagnosis and histological diagnosis was measured for surveillance intervals according to Dutch, European and American post-polypectomy surveillance guideline.Results Fifteen certified endoscopists participated in this study and included 3028 diminutive polyps. In 2,330 patients both optical and histological diagnosis were available. Optical diagnosis of diminutive polyps showed NPV of 84 % (95 % CI 80–87) for adenomatous histology in the rectosigmoid. Applying the ‘resect and discard’ strategy resulted in 90.6 %, 91.2 %, 90.9 % agreement on surveillance intervals for the Dutch, European and American guideline respectively.Conclusion Our data representing current clinical practice in the Dutch BCSP practice on optical diagnosis of diminutive polyps showed that accuracy of predicting histology remains challenging, and risk of incorrect optical diagnosis is still significant. Therefore, it is too early to safely implement these strategies.